Prevalence and morphometry of the fabella in cadaveric and radiological studies: Is there a link to knee osteoarthritis? - Ebru Yolaçan; Nurcan Ercıktı; Barış Baykal; Uğur Bozlar; Necdet Kocabıyık; Mehmet Ali Güner; Necati Salman; Ayşe Özdemir; Mislina Utlu; Laçin Ramazanlı (PLoS ONE, 2026)
Objective To investigate the morphometric features of the fabella in cadaveric specimens and evaluate its prevalence and potential association with knee osteoarthritis through radiological analysis. Methods In the cadaveric study, 65 knees from 32 cadavers and 3 leg specimens were dissected. Fabellas were measured and analyzed histologically. In the radiological study, bilateral knee X-rays of 1712 patients with osteoarthritis and 2304 control subjects were retrospectively reviewed. The presence and laterality of the fabella were recorded. Results Fabella was detected in 18.4% of dissected knees. No significant sex-based differences were found in morphometric measurements (p > 0.05). In the radiological study, the overall prevalence was 36.5% (37.6% in patients, 35.7% in controls), with no statistically significant association between fabella presence and osteoarthritis (p > 0.05). Lateralization patterns did not differ between groups. Conclusion This study provides the first morphometric data on fabella in Turkish cadavers and suggests no significant relationship between fabella presence and knee osteoarthritis. While fabella is a common anatomical variant, its clinical relevance in osteoarthritis remains inconclusive, warranting further investigation.